Retroperitoneal Leiomyosarcoma: Case report - López Camarena, Luis Miguel; Gutiérrez Sánchez, Paula Lizeth; Pérez Mena, Francisco Alejandro; Olvera Olvera, Marco Antonio; Esparza Cueva, Alejandro; Aguilar Espinosa, Francisco (Cirugía del Uruguay, 2024)
We present the case of a 57-year-old male patient with a retroperitoneal leiomyosarcoma found incidentally. It is a rare disease, with an annual incidence of 2.7 cases per million people. Likewise, it is a disease with a silent evolution, so it goes unnoticed until the tumor mass reaches a large size. Leiomyosarcomas appear as extensive areas of heterogeneity and heterogeneous enhancement, caused by the presence of necrosis and hemorrhagic foci. Normally, there is no presence of calcifications and there is an absence of adipose tissue, so a large retroperitoneal mass greater than 10 cm with no fat content and variable internal necrosis should suggest the possibility of a leiomyosarcoma. Complete surgical removal is the treatment of choice, and should be performed with wide negative margins, a factor that affects the prognosis, since these tumors tend to reach a very large size and wide excision is often impossible, which affects the patient's survival. This type of neoplasm has a poor prognosis, since it is known that the 5-year survival rate is approximately 15%, due to its high tendency to local invasion, metastasis or late diagnosis.